The Effect Of Application Of Cooperative Learning Model Type Pair Check On Learning Outcomes Student In The Mathematics Lesson Class IV SDN 351 Kawasan Amma Toa Kecamatan Kajang Bulukumba District - Yustika Yustika; Widya Karmila Sari Achmad; Erma Suryani Sahabuddin (International Journal of Elementary School Teacher, 2021)
This research is a research that uses a quantitative approach with the type of pre-experimental research and uses the form of One Group Pretest Posttest Design. The population in this study were all fourth grade students, totaling 16 students. The sample selection used is saturated sample technique. Data collection techniques in this study were observation sheets and tests. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis using Paired sample T-Test. The results showed that: (1) The learning process by applying the Pair Check type cooperative learning model can be said to be good, (2) student learning outcomes show an increase after applying the Pair Check type cooperative learning model in learning, (3) Pair Check type cooperative learning model has an effect on mathematics learning outcomes. Based on these results, it can be concluded that the Pair Check type of cooperative learning model has an effect on students' mathematics learning outcomes.